The need for health system strengthening in the wake of natural disasters: Lessons from the 2023 Türkiye-Syria earthquake - Emery Manirambona; Joseph Christian Obnial; Shuaibu Saidu Musa; Adriana Viola Miranda; Usman Abubakar Haruna; Deborah Oluwaseun Shomuyiwa (Wiley, 2023)
Abstract The 2023 Türkiye-Syria earthquake was reported as the largest earthquake of Mw7.8, resulting in over 50,783 and 7259 deaths in Turkey and Syria, respectively. It has also damaged numerous residential buildings and other essential infrastructures, thus rendering more than 850,000 children and 356,000 pregnant women homeless, forcing them into displacement and its dire consequences, such as inadequate temporary shelters, a lack of access to safe drinking water, sanitation and hygiene (WASH), necessary for disease prevention, health promotion and maintenance. The disaster has disproportionately affected the Syrian refugee community in Turkey as it has fuelled disparities and discrimination, exacerbating the response to the disaster and forcing refugees to return to Syria due to dire living conditions. Minimizing the effects of the disaster on the communities is therefore essential. There is a need to strengthen health system resilience and emergency response to natural disasters to reduce and prevent the aftermath. Disaster preparedness plans should include regulations that ensure that local buildings and infrastructure are disaster‐resistant. Furthermore, it is vital to highlight the importance of funding and appropriate resource allocation for disaster risk reduction. These include improving plans and logistics for recovery efforts, adequate preparation of temporary shelters and evacuation centres and allocating necessities such as food and water. Investment in proper search and rescue response, a special workforce for response and the rebuilding of important infrastructure are crucial. Finally, response to disasters must be inclusive and prioritize vulnerable populations, such as children, the aged women and refugees.